Disentangling the impact of anthropogenic and natural processes on the environment in a subtropical subalpine lake catchment in northeastern Taiwan over the past 150 years - Lin, Tsai-Wen; Kaboth-Bahr, Stefanie; Bahr, André; Yamoah, Kweku Afrifa; Su, Chih-Chieh; Wang, Liang-Chi; Wang, Pei-Ling; Löwemark, Ludvig (The science of the total environment, 2023)
Human activities impose significant changes on sedimentation processes and vegetation cover within lake catchments. However, the needed time for an anthropogenically disturbed natural state to be reversed back to its natural state by environmental protection programs is still ambiguous. Here we employ a multi-proxy approach to delineate major environmental disturbances such as logging and forest fires on the catchment in Cueifong Lake, a subtropical subalpine lake in northeastern Taiwan. X-ray Fluorescence (XRF) core scanning, bulk total organic carbon (TOC), bulk total nitrogen (TN), stable carbon isotope (δ13Corg) analysis, and macro-charcoal counting were utilized to reconstruct changes in the catchment environment based on a sediment core from Cueifong Lake. The results show that the element content changed distinctly around 1975 CE, which coincided with the onset of profound deforestation in the lake vicinity recorded in historical documents and aerial photos. After the cessation of the logging event, the detrital input increased, accompanied by decreasing C/N ratios and increasing δ13Corg values. This suggests that increased terrestrial nutrient input promoted algae growth. After the deforestation phase, our results imply a gradual recovery of elemental composition in the catchment environment. By extrapolating the XRF element records, we suggest that it might take >50 years for the sedimentary regime to reach its pre-logging baseline. In contrast to the depositional system, the C/N and δ13Corg shifted significantly - potentially irreversibly - towards an algae-dominant environment instead of recovering to the pre-logging condition. This could be due to both 1) the changes in the different vegetation species used for reforestation and/or 2) anthropogenically introduced fishes in the 1980s. This study proposes the first assessment of the needed recovery time for subtropical Asian subalpine forests after large-scale logging activity and thus provides an apparent reference for policy decisions on natural resource development and environmental protection.
Online veröffentlicht am 31. Dezember 2022, Artikelversion vom 10. Januar 2023
Gesehen am 16.11.2023